Conductive paste and preparation method thereof, carbon-coated current collector and preparation method and application thereof
By coating a modified carbon coating layer with oxygen-containing group on the surface of the positive electrode current collector aluminum foil of the lithium-ion battery, the problem of poor adhesion of the aluminum foil is solved, the cycle life and capacity of the battery is improved, and the carbon coating layer is enhanced conductivity and liquid retention properties.
Patent Information
- Application Number
- CN202411649671.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-18
AI Technical Summary
The positive electrode current collector aluminum foil commonly used in existing lithium-ion batteries has problems of poor adhesion and easy peeling, resulting in rapid attenuation of battery capacity and cycle life.
A carbon-coated current collector is used, and its carbon coating layer is composed of graphene oxide, modified graphene, modified carbon nanotubes, conductive carbon black and binder. The modified graphene and modified carbon nanotubes contain oxygen. The group is prepared by ultrasonic dispersion and sand grinding, and coated on the surface of the current collector body and dried to form a carbon coated current collector.
It improves the adhesion and conductivity of the carbon coated layer, extends the cycle life and capacity of the battery, reduces the amount of adhesive, and enhances the liquid retention and long-range conductivity of the carbon coated layer.
Smart Images

Figure CN119481079A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a conductive slurry and a preparation method thereof, a carbon-coated current collector and a preparation method and application thereof. Background Art
[0002] Secondary batteries can achieve cyclic charge and discharge and have become a current research hotspot. Among them, lithium-ion batteries in secondary batteries have been widely used in 3C digital, electric vehicles, energy storage and other aspects due to their many advantages such as high energy density, good cycle performance and light weight. In the field of lithium-ion batteries, aluminum foil is the most commonly used positive electrode current collector (that is, the current collector body), which can be used in combination with various positive electrode materials such as lithium cobalt oxide, lithium manganese oxide, ternary materials and lithium iron phosphate. However, conventional aluminum foil has certain problems in actual use, such as: the contact area with the positive electrode material in the positive electrode sheet is limited, which affects the internal resistance of the positive electrode sheet; the bonding strength between aluminum foil and binder and active material is limited. During the cyclic charge and discharge, the continuous change of electrode volume leads to loose bonding between particulate matter and easy powdering, which causes the battery capacity and cycle life to decay rapidly.
[0003] To improve the above problems, the current mainstream process is to first coat the positive electrode current collector with a 0.5-1 micron thick carbon coating layer, such as aluminum foil. This coating can provide excellent static conductivity, collect the microcurrent of the active material, thereby greatly reducing the contact resistance between the active material and the positive electrode current collector, and can improve the adhesion between the two due to the rougher surface, thereby significantly improving the overall performance of the battery.
[0004] At present, the commonly used conductive carbon materials in the carbon coating layer include graphene, carbon nanotubes (CNTs), conductive carbon black (SuperP), vapor-grown carbon fiber (VGCF), etc. However, they each have some defects. For example, the surface structure of graphene has problems such as difficulty in dispersion and easy agglomeration in processing, and as a sheet-like two-dimensional structure, it does not have good liquid retention and long-range conductivity. When it is used as a conductive agent for the carbon coating layer, its conductivity with the positive electrode current collector is poor, which has an adverse effect on the battery internal resistance, cycle performance and electrode processing performance. Carbon nanotubes have a certain aspect ratio and a high specific surface area, have excellent conductivity and can achieve long-range conductivity, but when used alone in the carbon coating layer, it is easy to peel off from the electrode and has poor compatibility with the slurry. Although conductive carbon black has cost advantages when used as a conductive agent for the carbon coating layer, it is used in large quantities, and the spherical conductive carbon black and the aluminum foil are in point-to-surface contact, and the small contact point is easy to cause poor contact and increase interface impedance. When graphene, carbon nanotubes, conductive carbon black and other conductive agents are mixed and dispersed, the planar structure of graphene is prone to adsorption with carbon nanotubes and conductive carbon black, and there are also problems such as difficulty in dispersion and easy agglomeration. Therefore, the carbon coating layer in the related art has at least the following technical problems: First, the carbon coating layer has poor adhesion and is easy to peel off. In order to improve the adhesion, the binder of the carbon conductive slurry is added, which will reduce the conductivity of the carbon coating layer; second, the conductive material in the carbon coating layer has poor dispersibility and is easy to agglomerate, so the conductivity and stability of the obtained carbon coating current collector are poor; third, in order to ensure conductivity, the carbon coating layer is thicker, which makes the bonding strength between the carbon coating layer and the positive electrode current collector poor. Summary of the invention
[0005] Based on this, the present application provides a conductive slurry and a preparation method thereof, a carbon-coated current collector and a preparation method and application thereof, in order to solve the technical problems in the related technology that the carbon-coated layer has poor adhesion and is easy to peel off, and adding a binder to improve adhesion will reduce conductivity, and the conductive material in the carbon-coated layer has poor dispersion and is easy to agglomerate, and the carbon-coated layer is thick.
[0006] In a first aspect, a carbon-coated current collector is provided, comprising a current collector body, and a carbon coating layer covering at least one side of the current collector body along its thickness direction, wherein the carbon coating layer comprises the following components: graphene oxide, modified graphene, modified carbon nanotubes, conductive carbon black and a binder in a mass ratio of (1~10):(10~45):(1~20):(1~10):(1~5), wherein the modified graphene and the modified carbon nanotubes both contain oxygen-containing groups.
[0007] Optionally, the oxygen-containing groups in the modified graphene and the oxygen-containing groups in the modified carbon nanotubes respectively include at least one of a hydroxyl group, a carboxyl group and a carbonyl group.
[0008] Optionally, the oxygen content in the carbon coating layer is 1% to 20%, and optionally 1% to 3%.
[0009] Optionally, the carbon-coated current collector satisfies at least one of the following conditions:
[0010] (1) A micro-nano pit structure is formed on at least one side of the surface of the current collector body along the thickness direction;
[0011] (2) The thickness of the current collector body is 4 μm to 20 μm;
[0012] (3) The current collector body is a single-layer structure or a multi-layer composite structure; optionally, the single-layer structure is an aluminum foil, and the multi-layer composite structure includes a polymer layer and aluminum coatings disposed on opposite sides of the polymer layer in a thickness direction;
[0013] (4) The thickness of the carbon coating layer is 0.5 μm to 5 μm;
[0014] (5) The surface dyne value of the carbon coating layer is higher than 40 dyn;
[0015] (6) The surface resistance of the carbon coating layer is less than 2.0Ω / sq.
[0016] In a second aspect, a conductive paste is provided, comprising: graphene oxide, modified graphene, modified carbon nanotubes, conductive carbon black, a binder and a solvent;
[0017] The mass ratio of the graphene oxide, the modified graphene, the modified carbon nanotube, the conductive carbon black, the binder and the solvent is (1-10): (10-45): (1-20): (1-10): (1-5): (3000-4000), and the modified graphene and the modified carbon nanotube both contain oxygen-containing groups.
[0018] Optionally, the modified graphene satisfies at least one of the following conditions:
[0019] (1) The oxygen-containing groups in the modified graphene include at least one of hydroxyl, carboxyl and carbonyl;
[0020] (2) The oxygen content in the modified graphene is 3% to 5%.
[0021] Optionally, the modified carbon nanotubes satisfy at least one of the following conditions:
[0022] (1) The oxygen-containing groups in the modified carbon nanotubes include at least one of hydroxyl, carboxyl and carbonyl groups;
[0023] (2) The oxygen content in the modified carbon nanotubes is 3% to 5%.
[0024] Optionally, the solvent comprises: ethanol and water in a volume ratio of (1-10):(1-10);
[0025] Optionally, the solvent further comprises an acid-base regulator, and the pH value of the solvent is 4-5;
[0026] Optionally, the acid-base regulator includes at least one of sulfuric acid, nitric acid and acetic acid.
[0027] In a third aspect, a method for preparing a conductive paste is provided, comprising:
[0028] Providing graphene oxide, modified graphene, modified carbon nanotubes and conductive carbon black, wherein the modified graphene and the modified carbon nanotubes both contain oxygen-containing groups;
[0029] Adding the graphene oxide, the modified graphene, the modified carbon nanotube, the conductive carbon black and a binder into the solvent, and preparing the conductive slurry by dispersing, grinding and filtering;
[0030] Wherein, the mass ratio of the graphene oxide, the modified graphene, the modified carbon nanotube, the conductive carbon black, the binder and the solvent is (1-10): (10-45): (1-20): (1-10): (1-5): (3000-4000).
[0031] Optionally, the modified graphene is prepared by oxidation reaction of graphene and dilute nitric acid; and / or,
[0032] The modified carbon nanotubes are prepared by oxidation reaction of carbon nanotubes and dilute nitric acid.
[0033] Optionally, the solvent is prepared by mixing ethanol and water in a volume ratio of (1-10):(1-10), and then adjusting the pH of the mixed solvent to 4-5 with an acid-base regulator.
[0034] Optionally, the preparation method satisfies at least one of the following conditions:
[0035] (1) dispersing the graphene oxide, the modified graphene, the modified carbon nanotubes, the conductive carbon black and the binder by ultrasound; optionally, the frequency of the ultrasound is 20 KHz to 40 KHz, and the time is 0.5 h to 1 h;
[0036] (2) The grinding is performed by sand milling, the grinding speed is 2000 rpm ~3000 rpm, the grinding and mixing time is 3 h ~ 24 h, and the grinding medium is 0.2 mm ~ 2 mm zirconia beads.
[0037] In a fourth aspect, a method for preparing a carbon-coated current collector is provided, comprising:
[0038] providing a current collector body;
[0039] Coating the conductive paste as described in the second aspect on at least one side of the current collector body along the thickness direction thereof;
[0040] The current collector body coated with the conductive slurry is dried, solidified and roll-pressed to prepare the carbon-coated current collector.
[0041] Optionally, before coating the conductive paste as described in the second aspect on at least one side of the current collector body along the thickness direction thereof, the method further comprises:
[0042] Cleaning the surface of the current collector body to remove the oxide layer and oil stains on the surface of the current collector body;
[0043] Optionally, the reagent used for the surface cleaning is a sodium hydroxide solution with a concentration of 10 g / L to 30 g / L, the cleaning temperature is 50° C. to 60° C., and the cleaning time is 0.5 h to 1 h;
[0044] Optionally, the drying method is electric ceramic drying, and the drying temperature is 70°C to 80°C;
[0045] Optionally, the coating method includes: at least one of spray coating, roller coating, dip coating, doctor blade coating, Meyer rod coating, electrospinning coating, and screen coating.
[0046] Optionally, the preparation method further comprises: performing a reduction treatment on the oxygen-containing groups in the carbon coating layer to remove the oxygen-containing groups in the carbon coating layer;
[0047] Optionally, the reducing agent used in the reduction treatment is hydroiodic acid.
[0048] In a fifth aspect, a use of the carbon-coated current collector as described in the first aspect in a secondary battery is provided.
[0049] Compared with the related art, this application has at least the following beneficial technical effects:
[0050] Since the carbon-coated layer in the carbon-coated current collector contains graphene oxide, modified graphene, modified carbon nanotubes, conductive carbon black and a binder, and both the modified graphene and the modified carbon nanotubes contain oxygen-containing groups, on the one hand, the modified graphene and the modified carbon nanotubes can maintain good conductivity, and at the same time, when the modified graphene and the modified carbon nanotubes are dispersed in the conductive slurry, the oxygen-containing groups can also improve the dispersion effect of the modified graphene and the modified carbon nanotubes in the conductive slurry, thereby improving the dispersion uniformity and stability of the modified graphene and the modified carbon nanotubes in the carbon-coated layer; on the other hand, the modified graphene is a two-dimensional carbon material, the modified carbon nanotubes are a one-dimensional carbon material, and the conductive carbon black is a zero-dimensional carbon material. When graphene, modified carbon nanotubes and conductive carbon black are mixed, a three-dimensional conductive network structure of points, lines and surfaces can be formed between the three, thereby improving the conductive effect of the carbon coating layer; on the other hand, the addition of graphene oxide can further improve the dispersion effect of modified graphene, modified carbon nanotubes and conductive carbon black in the conductive slurry, thereby further improving the dispersion uniformity and stability of each component in the carbon coating layer, and further improving the conductive effect. At the same time, the conductive carbon black can fill the gaps in the conductive network structure, thereby improving the structural continuity of the three-dimensional conductive network formed by modified graphene, modified carbon nanotubes and graphene oxide in the carbon coating layer, improving the density of the carbon coating layer, and further improving the conductivity of the carbon coating layer.
[0051] Furthermore, compared with the related art that uses graphene alone, such a sheet-like two-dimensional structure does not have good liquid retention and long-range conductivity, the carbon coating layer provided in the embodiment of the present application has good wettability and high conductivity. Therefore, the carbon coating layer provided in the embodiment of the present application has good liquid retention and long-range conductivity. By adding a small amount of binder, the adhesion between the carbon coating layer and the current collector body can be achieved. Compared with the carbon coating layer of the prior art, the amount of binder used is greatly reduced, which improves the conductivity of the carbon coating layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 The scanning electron microscope images of the carbon coating layer on the surface of the carbon-coated aluminum foil for lithium batteries provided in Examples 1 to 8 of the present application at different magnifications;
[0053] Figure 2 A schematic diagram of the surface microstructure simulation of the carbon-coated layer on the surface of the carbon-coated aluminum foil for lithium batteries provided in Examples 1 to 8 of the present application. DETAILED DESCRIPTION
[0054] In order to facilitate the understanding of the present application, the present application will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present application are given in the drawings. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0055] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0056] The present application will be further described in detail below in conjunction with specific embodiments. The present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present application more thoroughly understood.
[0057] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0058] In this application, "at least one" refers to any one, any two or any two or more of the listed items. Among them, "several" refers to any two or any two or more.
[0059] In the present application, the terms "combination thereof", "any combination thereof", "any combination thereof" and the like include all suitable combinations of any two or more of the listed items.
[0060] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0061] In the present application, reference to a numerical range includes both endpoints of the numerical range unless otherwise specified.
[0062] In the present application, the percentage content, unless otherwise specified, refers to mass percentage for solid-liquid mixing and solid-solid mixing, and volume percentage for liquid-liquid mixing.
[0063] In this application, when it comes to percentage concentration, unless otherwise specified, it refers to the final concentration. The final concentration refers to the proportion of the added component in the system after the addition of the component.
[0064] In this application, when it comes to temperature parameters, unless otherwise specified, both constant temperature treatment and treatment within a certain temperature range are permitted. The constant temperature treatment allows the temperature to fluctuate within the precision range controlled by the instrument.
[0065] Sources of some raw materials in the examples of this application:
[0066] Graphene: purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.;
[0067] Carbon nanotubes: purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.;
[0068] Conductive carbon black: purchased from Guangzhou Hengdeli New Energy Technology Co., Ltd.
[0069] Binder: specifically water-based acrylic resin, purchased from Guangdong Xidun New Material Technology Co., Ltd.
[0070] Unless otherwise specified, other raw materials are commercially available.
[0071] In view of the technical problems that the carbon coating layer in the related art has poor adhesion and is easy to peel off, the addition of a binder to improve adhesion will reduce conductivity, and the conductive material in the carbon coating layer has poor dispersion and is easy to agglomerate, and the carbon coating layer is thick, the specific implementation method of the present application is described as follows:
[0072] In a first aspect, some embodiments of the present application provide a carbon-coated current collector, which includes a current collector body and a carbon coating layer covering at least one side of the current collector body along its thickness direction, wherein the carbon coating layer includes the following components: graphene oxide, modified graphene, modified carbon nanotubes, conductive carbon black and a binder in a mass ratio of (1~10):(10~45):(1~20):(1~10):(1~5), wherein the modified graphene and the modified carbon nanotubes both contain oxygen-containing groups.
[0073] In the carbon-coated current collector provided in the embodiment of the present application, since the carbon-coated layer in the carbon-coated current collector contains graphene oxide, modified graphene, modified carbon nanotubes, conductive carbon black and a binder, the modified graphene and the modified carbon nanotubes both contain oxygen-containing groups. Therefore, on the one hand, the modified graphene and the modified carbon nanotubes can maintain good conductivity. At the same time, when the modified graphene and the modified carbon nanotubes are dispersed in the conductive slurry, the oxygen-containing groups can also improve the dispersion effect of the modified graphene and the modified carbon nanotubes in the conductive slurry, thereby improving the dispersion uniformity and stability of the modified graphene and the modified carbon nanotubes in the carbon-coated layer; on the other hand, the modified graphene is a two-dimensional carbon material, the modified carbon nanotubes are a one-dimensional carbon material, and the conductive carbon black is a zero-dimensional carbon. When modified graphene, modified carbon nanotubes and conductive carbon black are mixed, a three-dimensional conductive network structure of points, lines and surfaces can be formed between the three, thereby improving the conductive effect of the carbon coating layer; on the other hand, the addition of graphene oxide can further improve the dispersion effect of modified graphene, modified carbon nanotubes and conductive carbon black in the conductive slurry, thereby further improving the dispersion uniformity and stability of each component in the carbon coating layer, and further improving the conductive effect. At the same time, the conductive carbon black can fill the gaps in the conductive network structure, thereby improving the structural continuity of the three-dimensional conductive network formed by the modified graphene, modified carbon nanotubes and graphene oxide in the carbon coating layer, improving the density of the carbon coating layer, and further improving the conductivity of the carbon coating layer.
[0074] Furthermore, compared with the related art that uses graphene alone, such a sheet-like two-dimensional structure does not have good liquid retention and long-range conductivity, the carbon coating layer provided in the embodiment of the present application has good wettability and high conductivity. Therefore, the carbon coating layer provided in the embodiment of the present application has good liquid retention and long-range conductivity. By adding a small amount of binder, the adhesion between the carbon coating layer and the current collector body can be achieved. Compared with the carbon coating layer of the prior art, the amount of binder used is greatly reduced, which improves the conductivity of the carbon coating layer.
[0075] In summary, the carbon-coated current collector provided in the embodiments of the present application solves the technical problems in the related art that the carbon-coated layer has poor adhesion and is easy to peel off, the addition of a binder to improve adhesion will reduce conductivity, the conductive material in the carbon-coated layer has poor dispersion and is easy to agglomerate, and the carbon-coated layer is relatively thick.
[0076] In some embodiments, the oxygen-containing groups in the modified graphene and modified carbon nanotubes respectively include at least one of a hydroxyl group, a carboxyl group and a carbonyl group.
[0077] In these embodiments, these oxygen-containing groups can react with some oxygen-containing functional groups in graphene oxide, thereby facilitating uniform dispersion of the modified graphene and the modified carbon nanotubes in the conductive paste and the carbon coating layer.
[0078] In some embodiments, the oxygen content in the carbon coating layer is 1% to 20%, and can be 1% to 3%. For example, the oxygen content in the carbon coating layer can be 1%, 2%, 3%, 5%, 8%, 10%, 15%, 20%, 25%, 30%, or any value between any two of the foregoing.
[0079] In these embodiments, the oxygen content in the carbon coating layer refers to the mass ratio of oxygen element to the total weight of the carbon coating layer components. By controlling the oxygen content in the carbon coating layer to 1% to 20%, the carbon coating layer can be kept with excellent electrical conductivity while ensuring that the components in the carbon coating layer are evenly dispersed.
[0080] In some embodiments, the carbon-coated current collector satisfies at least one of the following conditions:
[0081] (1) A micro-nano pit structure is formed on at least one side of the surface of the current collector body along the thickness direction;
[0082] (2) The thickness of the current collector body is 4 μm to 20 μm; it can be 5 μm to 15 μm. For example, the thickness of the current collector body can be 4 μm, 5 μm, 6 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, or any value between any two of the foregoing.
[0083] (3) The current collector body is a single-layer structure or a multi-layer composite structure;
[0084] (4) The thickness of the carbon coating layer is 0.5 μm ~ 5 μm; it can be 0.5 ~ 2 μm. For example, the thickness of the carbon coating layer can be 0.5 μm, 0.8 μm, 1 μm, 1.2 μm, 1.5 μm, 2 μm, 3 μm, 4 μm, 5 μm or any value between any two of the foregoing.
[0085] (5) The surface dyne value of the carbon coating layer is higher than 40 dyn, which can be selected from 40 dyn to 50 dyn. For example, the surface dyne value of the carbon coating layer can be 41 dyn, 42 dyn, 45 dyn, 46 dyn, 48 dyn, 50 dyn or any value between any two of the above.
[0086] (6) The surface resistance of the carbon coating layer is less than 2.0Ω / sq. For example, the surface resistance of the carbon coating layer may be 0.5Ω / sq, 1.0Ω / sq, 1.5Ω / sq, 1.8Ω / sq, or any value between any two of the foregoing.
[0087] In these embodiments, a micro-nano pit structure is formed on the surface of at least one side of the current collector body along its thickness direction, which is conducive to the adhesion of the carbon coating layer to at least one side of the current collector body along its thickness direction, and improves the adhesion of the carbon coating layer on the current collector body, thereby further reducing the contact resistance between the carbon coating layer and the current collector body, and improving the conductivity of the carbon-coated current collector. The current collector body can be a metal single-layer structure, or a metal / polymer laminated structure. By controlling the thickness of the carbon coating layer within the range of 0.5μm ~ 5μm, the carbon coating layer can be kept at a small thickness while ensuring that the carbon coating layer has good conductivity, thereby reducing the probability of peeling between the carbon coating layer and the current collector body. The surface dyne value of the carbon coating layer is higher than 40dyn, which can effectively improve the surface wetting properties of the carbon coating layer, thereby improving the adhesion properties between the active material and the current collector body. The surface square resistance of the carbon coating layer is less than 2.0Ω / sq, which can effectively improve the conductivity of the carbon-coated current collector.
[0088] In some optional embodiments, the single-layer structure is a single-layer aluminum foil, and the multi-layer composite structure includes a polymer layer and aluminum coatings disposed on opposite sides of the polymer layer in a thickness direction.
[0089] In a second aspect, some embodiments of the present application provide a conductive paste, which includes: graphene oxide, modified graphene, modified carbon nanotubes, conductive carbon black, a binder, and a solvent. The mass ratio of graphene oxide, modified graphene, modified carbon nanotubes, conductive carbon black, a binder, and a solvent is (1-10): (10-45): (1-20): (1-10): (1-5): (3000-4000), and both the modified graphene and the modified carbon nanotubes contain oxygen-containing groups.
[0090] In the conductive paste provided in the embodiment of the present application, on the one hand, graphene oxide acts as a dispersant, which can improve the dispersion effect of modified graphene, modified carbon nanotubes and conductive carbon black in the conductive paste, thereby improving the dispersion uniformity and stability of modified graphene, modified carbon nanotubes and conductive carbon black in the conductive paste; on the other hand, modified graphene, modified carbon nanotubes and conductive carbon black can form a three-dimensional conductive network structure of points, lines and surfaces in the conductive paste, thereby improving the conductive performance of the carbon coating layer. At the same time, conductive carbon black can fill the gaps in the conductive network structure, thereby improving the density of these carbon materials. Furthermore, the structural continuity of the three-dimensional conductive network of the carbon coating layer and the density of the carbon coating layer can be improved, and the conductivity of the carbon coating layer can be improved; thirdly, by limiting the mass ratio of graphene oxide, modified graphene, modified carbon nanotubes, conductive carbon black, binder and solvent within the above range, it is convenient to increase the viscosity of the conductive slurry, thereby facilitating the adhesion of the conductive slurry to the surface of the current collector body, thereby improving the bonding performance of the conductive slurry with the current collector body and avoiding the carbon coating layer from peeling off from the current collector body; at the same time, the conductive slurry has good leveling effect and coating effect, and can prepare a carbon coating layer with thinner thickness and better conductive performance.
[0091] In some embodiments, the modified graphene satisfies at least one of the following conditions:
[0092] (1) The oxygen-containing groups in the modified graphene include at least one of hydroxyl, carboxyl and carbonyl groups;
[0093] (2) The oxygen content in the modified graphene is 3% to 5%. For example, the oxygen content in the modified graphene may be 3%, 4% or 5%.
[0094] The oxygen content in the modified graphene refers to the mass ratio of the oxygen element in the modified graphene to the weight of the modified graphene.
[0095] In these embodiments, when the modified graphene is dispersed in the conductive paste, these oxygen-containing groups can react with graphene oxide, thereby improving the dispersion uniformity and stability of the modified graphene in the conductive paste; by controlling the oxygen content of the modified graphene to 3%~5%, the oxygen content in the conductive paste and the carbon coating layer prepared from the conductive paste can be controlled, thereby ensuring that the modified graphene is dispersed uniformly and stably in the carbon coating layer while maintaining the excellent conductive properties of the modified graphene.
[0096] In some embodiments, the modified carbon nanotubes satisfy at least one of the following conditions:
[0097] (1) The oxygen-containing groups in the modified carbon nanotubes include at least one of a hydroxyl group, a carboxyl group and a carbonyl group;
[0098] (2) The oxygen content in the modified carbon nanotubes is 3% to 5%. For example, the oxygen content in the modified carbon nanotubes may be 3%, 4% or 5%.
[0099] The oxygen content in the modified carbon nanotubes refers to the mass ratio of the oxygen element in the modified carbon nanotubes to the weight of the modified carbon nanotubes.
[0100] In these embodiments, when the modified carbon nanotubes are dispersed in the conductive paste, these oxygen-containing groups can react with graphene oxide, thereby improving the dispersion uniformity and stability of the modified carbon nanotubes in the conductive paste; by controlling the oxygen content of the modified carbon nanotubes to 3%~5%, the oxygen content in the conductive paste and the carbon coating layer prepared from the conductive paste can be controlled, thereby ensuring that the modified carbon nanotubes are dispersed uniformly and stably in the carbon coating layer while maintaining the excellent conductive properties of the modified carbon nanotubes.
[0101] In some embodiments, the modified carbon nanotubes may include at least one of modified single-walled carbon nanotubes (SWCNTs) and modified multi-walled carbon nanotubes (MWCNTs).
[0102] In some embodiments, the oxygen content of the graphene oxide is 10% to 20%. For example, the oxygen content of the graphene oxide can be 10%, 12%, 15%, 18%, 20%, or any value between any two of the foregoing.
[0103] The oxygen content of the graphene oxide refers to the mass ratio of the oxygen element in the graphene oxide to the weight of the graphene oxide.
[0104] In some embodiments, the conductive carbon black satisfies at least one of the following conditions:
[0105] (1) The D50 particle size of conductive carbon black is 50 nm ~300 nm;
[0106] (2) The initial conductivity of conductive carbon black is 100 S / m~200 S / m.
[0107] For example, the D50 particle size of the conductive carbon black is 50 nm, 80 nm, 100 nm, 150 nm, 200 nm, 300 nm or any value between any two of the foregoing, and the initial conductivity is 100 S / m, 110 S / m, 150 S / m, 180 S / m, 200 S / m or any value between any two of the foregoing.
[0108] The D50 particle size can be obtained by testing with a laser particle size distribution instrument. The D50 particle size indicates the particle size corresponding to when the cumulative volume distribution percentage of conductive carbon black reaches 50%.
[0109] In some embodiments, the binder is at least one of water-based acrylic resin, polyurethane resin, vinyl acetate resin, hydroxypropyl methylcellulose, ethyl cellulose, carboxymethyl cellulose, polyvinyl alcohol, polyethylene glycol, starch and protein;
[0110] Optionally, the binder is at least one of water-based acrylic resin, hydroxypropyl methylcellulose, and polyvinyl alcohol.
[0111] In some embodiments, the solvent includes: ethanol and water in a volume ratio of (1-10):(1-10). Specifically, the ethanol is 75% ethanol by volume, and the water is deionized water.
[0112] In some optional embodiments, the solvent further includes an acid-base regulator, and the pH value of the solvent is 4-5.
[0113] In these embodiments, by adjusting the pH value of the solvent to 4-5, when the conductive slurry is coated on the current collector body, the conductive slurry can corrode the surface of the current collector body, thereby forming a micro-nano pit structure on the surface of the current collector body. The micro-nano pit structure is beneficial to improving the adhesion performance of the conductive slurry on the current collector body, thereby further improving the bonding firmness between the carbon coating layer and the current collector body, and preventing the carbon coating layer from peeling off from the current collector body.
[0114] In some embodiments, the acid-base regulator includes at least one of sulfuric acid, nitric acid, and acetic acid.
[0115] In some embodiments, the viscosity of the conductive paste is 200 Pa·s-2000 mPa·s, and / or the fineness of the conductive paste is less than 20 μm.
[0116] In these embodiments, by controlling the viscosity of the conductive paste within the range of 200 Pa·s to 2000 mPa·s, the bonding strength between the conductive paste and the current collector can be improved; by controlling the fineness of the conductive paste to less than 20 μm, the density and conductivity of the carbon coating layer can be improved.
[0117] In a third aspect, some embodiments of the present application provide a method for preparing a conductive paste, the preparation method comprising:
[0118] S11), providing graphene oxide, modified graphene, modified carbon nanotubes and conductive carbon black, wherein the modified graphene and the modified carbon nanotubes both contain oxygen-containing groups;
[0119] S12), adding graphene oxide, modified graphene, modified carbon nanotubes, conductive carbon black and a binder into a solvent, and preparing a conductive slurry by dispersing, grinding and filtering;
[0120] Among them, the mass ratio of graphene oxide, modified graphene, modified carbon nanotubes, conductive carbon black, binder and solvent is (1~10):(10~45):(1~20):(1~10):(1~5):(3000~4000).
[0121] In the method for preparing the conductive paste provided in the embodiment of the present application, graphene oxide, modified graphene, modified carbon nanotubes, conductive carbon black and a binder are added to a solvent, and the conductive paste is prepared by dispersing, grinding and filtering.
[0122] In some embodiments, the modified graphene is prepared by oxidation reaction of graphene and dilute nitric acid; and / or, the modified carbon nanotubes are prepared by oxidation reaction of carbon nanotubes and dilute nitric acid.
[0123] In these embodiments, the graphene and / or carbon nanotubes are modified and grafted with a small amount of oxygen-containing groups, which can improve the dispersion performance of the modified graphene and / or modified carbon nanotubes in the conductive paste while maintaining good conductive properties.
[0124] In some embodiments, when preparing modified graphene, the number of graphene layers can be 1 to 10 layers, the sheet size of each layer can be 0.1 μm to 10 μm, and / or the conductivity of the graphene is 15000 S / m to 25000 S / m, and / or the graphene is prepared by mechanical exfoliation, and / or the concentration of dilute nitric acid is 30% to 40%, and / or the temperature of the oxidation reaction is 25°C to 35°C, the time is 0.5h to 2h, and / or the solid-liquid ratio of the oxidation reaction is 1:300 to 1:200.
[0125] Among them, the number of graphene layers can be 1 to 10 layers, which means that graphene with 1 to 10 layers can be selected; the sheet size of each layer can be 0.1 μm to 10 μm, which means that graphene with an average sheet size of 0.1 μm to 10 μm can be selected; the conductivity of graphene is 15000 S / m to 25000 S / m, which means that the conductivity of the modified graphene is tested to be any value between 15000 S / m and 25000 S / m. The solid-liquid ratio of the oxidation reaction refers to the mass ratio of solid to liquid, and here refers to the mass ratio of graphene to dilute nitric acid solution.
[0126] The concentration of dilute nitric acid here refers to the mass percentage of nitric acid in the dilute nitric acid.
[0127] In these embodiments, by controlling the physicochemical properties of the reaction raw materials, the physicochemical properties of the reaction product can be adjusted, so that modified graphene grafted with a small amount of oxygen-containing groups can be obtained.
[0128] In some embodiments, when preparing modified carbon nanotubes, the length of the carbon nanotubes is 5μm~50μm, the inner diameter is 1nm~30nm, the initial conductivity is 500 S / m~1000S / m, and / or the carbon nanotubes include at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes, and / or the concentration of dilute nitric acid is 30%~40%, and / or the temperature of the oxidation reaction is 25℃~35℃, the time is 0.5h~2h, and / or the solid-liquid ratio of the oxidation reaction is 1:300~1:200.
[0129] Among them, the length of the carbon nanotube refers to the average length; the inner diameter of the carbon nanotube is 1nm~30nm, which means that the average inner diameter of the carbon nanotube is any value between 1nm~30nm; the initial conductivity of the carbon nanotube is 500 S / m~1000S / m, which means that the initial conductivity of the carbon nanotube used for modification is any value between 500 S / m~1000S / m after testing. The solid-liquid ratio of the oxidation reaction refers to the mass ratio of the solid to the liquid, and here refers to the mass ratio of the carbon nanotube to the dilute nitric acid solution.
[0130] The concentration of dilute nitric acid here refers to the mass percentage of nitric acid in the dilute nitric acid.
[0131] In these embodiments, the physicochemical properties of the reaction raw materials are controlled to adjust the physicochemical properties of the reaction products, thereby obtaining modified carbon nanotubes grafted with a small amount of oxygen-containing groups.
[0132] In some embodiments, the conductive carbon black can be purchased directly, and its D50 particle size is 50 nm to 300 nm, and its initial conductivity is 100 S / m to 200 S / m.
[0133] Here, the D50 particle size of the conductive carbon black is 50nm~300nm, which means that the D50 particle size of the conductive carbon black can be any value between 50nm~300nm. The initial conductivity is 100 S / m~200S / m, which means that the initial conductivity of the conductive carbon black is any value between 100 S / m~200S / m.
[0134] In some embodiments, the graphene oxide can be prepared by using flake graphite through the Hummers method; optionally, the size of the flake graphite can be 8000 mesh to 16000 mesh.
[0135] In some embodiments, the solvent is prepared by mixing ethanol and water in a volume ratio of (1-10):(1-10), and then adjusting the pH of the mixed solvent to 4-5 with an acid-base regulator.
[0136] In some embodiments, the above preparation method satisfies at least one of the following conditions:
[0137] (1) dispersing graphene oxide, modified graphene, modified carbon nanotubes, conductive carbon black and a binder by ultrasound; optionally, the frequency of the ultrasound is 20 KHz to 40 KHz, and the time is 0.5 h to 1 h;
[0138] (2) The grinding is carried out by sand milling, the grinding speed is 2000 rpm ~3000 rpm, the grinding and mixing time is 3 h ~ 24 h, and the grinding medium is 0.2 mm ~ 2 mm zirconia beads.
[0139] In a fourth aspect, some embodiments of the present application provide a method for preparing a carbon-coated current collector, the preparation method comprising:
[0140] S21), providing a current collector body;
[0141] The current collector body may be a single-layer structure or a multi-layer composite structure, which is not specifically limited here.
[0142] For example, when the current collector body is a single-layer structure, the current collector body may be an aluminum foil; when the current collector body is a multi-layer composite structure, the current collector body may include a polymer layer and aluminum coatings disposed on opposite sides of the polymer layer in a thickness direction.
[0143] Optionally, the thickness of the current collector body may be 4 μm to 20 μm.
[0144] S22), coating the conductive paste as described in the second aspect on at least one side of the current collector body along its thickness direction;
[0145] Optionally, the coating method includes at least one of spray coating, roller coating, dip coating, doctor blade coating, Meyer rod coating, electrostatic spinning coating and screen coating.
[0146] S23), drying, curing and rolling the current collector body coated with the conductive slurry to prepare a carbon-coated current collector.
[0147] Optionally, the drying method is electric ceramic drying, and the drying temperature can be 70°C to 80°C;
[0148] In the preparation method of the carbon-coated current collector provided in the embodiment of the present application, a carbon-coated layer can be formed on at least one side of the current collector body along its thickness direction by coating, drying and curing, and rolling. The preparation method is simple and facilitates the close combination of the conductive slurry and the current collector body.
[0149] In some embodiments, in S22), before coating the conductive paste as described in the second aspect on at least one side of the current collector body along its thickness direction, the method may further include:
[0150] The surface of the current collector body is cleaned to remove the oxide layer and oil stains on the surface of the current collector body.
[0151] In these embodiments, the conductive slurry is facilitated to adhere to the surface of the current collector body, and the contact resistance between the carbon-coated layer and the current collector body is reduced, thereby improving the conductive performance of the carbon-coated current collector.
[0152] In some embodiments, the reagent used for surface cleaning is a sodium hydroxide solution with a concentration of 10 g / L to 30 g / L, the cleaning temperature is 50° C. to 60° C., and the cleaning time is 0.5 h to 1 h.
[0153] In the preparation method of the carbon-coated current collector provided in an embodiment of the present application, the carbon-coated current collector is prepared by coating the conductive slurry as described in the second aspect on at least one side of the current collector body along its thickness direction, and drying, curing and rolling. The carbon-coated current collector includes a current collector body and a carbon coating layer covering at least one side of the current collector body along its thickness direction. The carbon coating layer includes: graphene oxide, modified graphene, modified carbon nanotubes, conductive carbon black and a binder in a mass ratio of (1~10):(10~45):(1~20):(1~10):(1~5), wherein the modified graphene and the modified carbon nanotubes both contain oxygen-containing groups.
[0154] Through testing, it was found that the oxygen content in the carbon coating layer is 15% to 20%. The oxygen content in the carbon coating layer refers to the mass ratio of the oxygen element in the carbon coating layer to the total weight of the carbon coating layer.
[0155] In some embodiments, the preparation method further comprises: performing a reduction treatment on the oxygen-containing groups in the carbon coating layer to remove the oxygen-containing groups in the carbon coating layer.
[0156] In these embodiments, the conductivity of the carbon coating layer can be further improved by performing a reduction treatment on the oxygen-containing groups in the carbon coating layer to remove the oxygen-containing groups in the carbon coating layer.
[0157] In some embodiments, the reducing agent used in the reduction treatment is hydroiodic acid.
[0158] In these embodiments, hydroiodic acid undergoes a redox reaction with oxygen-containing groups in the carbon coating layer, and oxygen-containing groups such as hydroxyl groups in the carbon coating layer undergo a halogenation substitution reaction under the action of hydroiodic acid, thereby removing the oxygen-containing functional groups in the carbon coating layer, thereby reducing the surface resistivity of the carbon coating layer.
[0159] After the oxygen-containing groups in the carbon coating were reduced, the test found that the oxygen content in the carbon coating was reduced to 1%~3%. The oxygen content here also refers to the mass ratio of the oxygen element in the carbon coating to the total weight of the carbon coating.
[0160] In a fifth aspect, some embodiments of the present application provide an application of a carbon-coated current collector as described in the first aspect in a secondary battery.
[0161] The surface of the carbon-coated current collector has a porous structure, which can effectively improve the adhesion performance of the positive or negative electrode active material thereon, thereby improving the energy density, cycle stability and rate performance of the secondary battery.
[0162] Wherein, the secondary battery can be a sodium ion battery or a lithium ion battery.
[0163] The above introduces the specific implementation methods of the present application. In order to objectively illustrate the technical effects produced by the present application, the following examples and comparative examples will be used for description.
[0164] In the following examples and comparative examples, all raw materials can be purchased in commercial form, and in order to maintain the reliability of the experiment, the raw materials used in the following examples and comparative examples have the same physical and chemical parameters or are processed in the same way.
[0165] Example 1
[0166] The preparation method of the conductive paste provided in this embodiment comprises the following steps:
[0167] (1) Preparation of graphene oxide (GO) by the traditional Hummers method: 10 g of 8000 mesh flake graphite was weighed and mixed with 1 L of concentrated sulfuric acid in a reactor. The mixture was stirred at 300 r / min for 30 min in an ice-water bath at 0 °C. Then 40 g of potassium permanganate was slowly added and stirred for 1 h. The temperature of the reactor was controlled at 40 °C. 1 L of deionized water was slowly added and stirred for 30 min. Finally, an appropriate amount of hydrogen peroxide was added to reduce the residual oxidant until the solution turned bright yellow. Stirring was continued for 10 min to complete the reaction. The supernatant was removed by hot filter press. The solid product was washed and filtered several times with deionized water until the pH of the washing solution was 4. The solid product was freeze-dried to obtain a yellow-brown GO solid for later use.
[0168] (2) Graphene (GNP) modification and grafting treatment: Weigh 50 g of a few-layer graphene powder with 1 to 5 layers, an average sheet size of 6 μm per layer, and an electrical conductivity of 20,000 S / m and 1.2 L of 40% dilute nitric acid, and stir and react them in a reactor at 25°C for 1 h. After the carboxylation reaction is completed, wash and filter with deionized water for multiple times until the pH of the washing liquid is 4. After drying, the modified graphene (modified GNP) is obtained and set aside.
[0169] (3) Carbon nanotube (CNT) modification and grafting treatment: Weigh 50 g of multi-walled carbon nanotube (MWCNTs) powder with an average length of 25 μm, an average inner diameter of 6 nm, and an electrical conductivity of 1000 S / m and 1.2 L of 40% dilute nitric acid, and stir and react them in a reactor at 25°C for 1 h. After the carboxylation reaction of the multi-walled carbon nanotube is completed, wash and filter with deionized water for multiple times until the pH of the washing liquid is 4. After drying, the modified multi-walled carbon nanotube (modified MWCNTs) is obtained and set aside;
[0170] (4) Pre-dispersion: 1 L of ethanol and 3 L of deionized water were taken as a mixed solvent, and the pH of the mixed solvent was adjusted to 4 with sulfuric acid as an acid-base regulator. 5 g of GO, 20 g of modified GNPs, 5 g of modified MWCNTs, 5 g of conductive carbon black with a D50 particle size of 100 nm, and 1 g of aqueous acrylic resin were weighed and added to the mixed solvent for ultrasonic pre-dispersion. The ultrasonic frequency was 40 kHz and the pre-dispersion time was 1 h.
[0171] (5) Grinding and blending: The pre-dispersed liquid was put into a sand mill for grinding, blending and grafting, and the mixture was ground and mixed at a speed of 3000 rpm for 6 h;
[0172] (6) Filter the slurry with an 800-mesh screen and collect the conductive slurry for later use. The fineness of the conductive slurry is less than 20 μm.
[0173] The method for preparing the carbon-coated current collector provided in this embodiment comprises the following steps:
[0174] (7) Providing rolled aluminum foil with a thickness of 8 μm for standby use;
[0175] (8) After the rolled aluminum foil is unrolled, it enters the cleaning tank to clean the surface. The cleaning tank contains a sodium hydroxide solution with a concentration of 20g / L and a cleaning temperature of 60°C. After cleaning for 0.5h, it enters the drying process;
[0176] (9) The conductive paste provided in this embodiment is used as a precursor, and a spray coating process is adopted to coat the surface of the cleaned aluminum foil. The thickness of the carbon coating layer on both sides is controlled to be 2 μm by controlling the spray flow rate and the spray time. The aluminum foil loaded with the conductive paste is dried (75°C), cured and rolled to obtain a carbon-coated aluminum foil for lithium batteries.
[0177] Example 2
[0178] Embodiment 2 is basically the same as Embodiment 1, except that:
[0179] In step (4), 5 g GO, 20 g modified GNPs, 5 g modified MWCNTs, 5 g conductive carbon black and 2 g aqueous acrylic resin were weighed and added into a mixed solvent for ultrasonic pre-dispersion.
[0180] Example 3
[0181] Embodiment 3 is basically the same as Embodiment 1, except that:
[0182] In step (4), 5 g GO, 20 g modified GNPs, 5 g modified MWCNTs, 5 g conductive carbon black and 5 g aqueous acrylic resin were weighed and added into a mixed solvent for ultrasonic pre-dispersion.
[0183] Example 4
[0184] Embodiment 4 is substantially the same as Embodiment 1, except that:
[0185] In step (4), 1 g GO, 10 g modified GNPs, 1 g modified MWCNTs, 1 g conductive carbon black with a D50 particle size of 100 nm and 1 g aqueous acrylic resin are weighed and added into a mixed solvent for ultrasonic pre-dispersion;
[0186] In step (8), the cleaning tank contains a sodium hydroxide solution with a concentration of 10 g / L and a cleaning temperature of 50°C. After cleaning for 1 hour, the drying process begins.
[0187] In step (9), the thickness of the carbon coating layer is 0.5 μm and the drying temperature is 70° C.
[0188] Example 5
[0189] Embodiment 5 is substantially the same as Embodiment 1, except that:
[0190] In step (4), 10 g GO, 40 g modified GNPs, 20 g modified MWCNTs, 10 g conductive carbon black with a D50 particle size of 100 nm and 5 g aqueous acrylic resin were weighed and added into a mixed solvent for ultrasonic pre-dispersion at an ultrasonic frequency of 25 KHz for a pre-dispersion time of 0.8 h.
[0191] In step (5), the pre-dispersed liquid is put into a sand mill for grinding, blending and grafting, and the grinding and mixing is carried out at a speed of 2500 rpm for 24 hours;
[0192] In step (8), the cleaning tank contains a sodium hydroxide solution with a concentration of 30 g / L and a cleaning temperature of 55°C. After cleaning for 0.6 h, the drying process begins.
[0193] In step (9), the thickness of the carbon coating layer is 5 μm and the drying temperature is 80° C.
[0194] Example 6
[0195] Embodiment 6 is basically the same as Embodiment 1, except that:
[0196] In step (9), after the carbon coating layer is dried and solidified, a hydroiodic acid (HI) reduction process is added.
[0197] Example 7
[0198] Example 7 is basically the same as Example 1, except that:
[0199] In step (7), the aluminum foil used is a composite aluminum foil with a thickness of 10 μm, an 8 μm PET middle layer, and 1 μm evaporated aluminum layers on both sides.
[0200] Example 8
[0201] The preparation method of the carbon-coated current collector in Example 8 is substantially the same as the preparation method of the carbon-coated current collector in Example 1, except that:
[0202] In step (4), no acid-base regulator is used to adjust the pH of the mixed solvent.
[0203] Comparative Example 1
[0204] This comparative example is basically the same as Example 1, except that:
[0205] In the preparation method of the conductive paste, graphene does not go through step (2), carbon nanotubes do not go through step (3), and neither is treated with nitric acid, and are directly used as raw materials for preparing the conductive paste. That is, 5g GO, 20g GNP, 5g MWCNTs, 5g conductive carbon black and 1g aqueous acrylic resin are weighed and added into a mixed solvent for ultrasonic pre-dispersion.
[0206] Comparative Example 2
[0207] This comparative example is basically the same as Example 1, except that:
[0208] In the preparation method of the conductive slurry, graphene oxide was not added as a dispersant, that is, 20 g of modified GNPs, 5 g of modified MWCNTs, 5 g of conductive carbon black and 1 g of aqueous acrylic resin were added to a mixed solvent for ultrasonic pre-dispersion.
[0209] Test Case
[0210] The carbon-coated aluminum foils for lithium batteries provided in Examples 1 to 8 and Comparative Examples 1 to 2 were subjected to performance tests. The specific test methods and test results are as follows:
[0211] 1. The surface microscopic morphology of the carbon-coated layer on the surface of the carbon-coated aluminum foil for lithium batteries provided in Examples 1 to 8 was observed by a high-power scanning electron microscope, and the test results at different magnifications were obtained as follows: Figure 1 As shown, the scale bar in the left figure is 1 μm, and the scale bar in the right figure is 200 nm.
[0212] Depend on Figure 1 It can be seen from the left and right figures in the figure that the modified GNPs and modified MWCNTs in the carbon coating layer can complement each other. The modified MWCNTs can overlap each other to form a mesh bridge structure, and can also be embedded or attached to GO and modified GNPs to repair the line defects on GO and modified GNPs, providing a one-dimensional conductive channel for carriers; GO and modified GNPs themselves can also be stacked in an orderly manner and overlap each other on the basis of the modified MWCNTs mesh structure to form a conductive path. GO and modified GNPs can either fill in the gaps in the modified MWCNTs mesh structure, or be loaded on the overlap nodes of the modified MWCNTs, or cover the entire mesh structure in a large area. This complementary overlap between the two can not only reduce the contact resistance of the carbon coating layer, but also enhance the structural stability of the carbon coating layer. The conductive carbon black particles are attached to the exposed modified MWCNTs or GO and modified GNPs, further filling the gaps in the conductive network structure, making the microscopic morphology of the carbon coating layer more dense and continuous, thereby reducing the contact resistance. The schematic diagram of the surface microstructure simulation of the carbon coating layer on the surface of the carbon-coated aluminum foil for lithium batteries provided in Examples 1 to 8 is shown in FIG. Figure 2 shown.
[0213] 2. Testing the oxygen content of the carbon-coated layer in the carbon-coated aluminum foil provided in Example 1 by infrared spectroscopy: Detecting the oxygen-containing functional groups of the carbon-coated layer in the carbon-coated aluminum foil provided in Example 1 by infrared spectroscopy, and calculating the oxygen content in the raw material and the carbon-coated layer according to the type and content of the oxygen-containing functional groups.
[0214] The specific test results are as follows: the original GNPs do not have any oxygen-containing functional groups, but after being treated with dilute HNO 3 After soaking in water, the -OH group (3735cm -1 )、C=O group(1794cm -1 ), part of the double bond structure in the benzene ring is broken, forming a CH single bond (2923cm -1 ) and CC groups (1384 cm -1 The original MWCNTs surface already has a small amount of hydroxyl groups (3416cm -1 ), after dilute HNO 3 After immersion treatment, C=O groups (1654 cm -1). It can be seen that a few oxygen-containing groups can be attached to the surface of GNPs and MWCNTs by simply soaking in dilute nitric acid. These oxygen-containing groups can react with some oxygen-containing functional groups on GO during the grinding and mixing process, so that the hydrophobic GNPs and MWCNTs can be stably dispersed in the mixed solvent to obtain a conductive slurry with stable performance.
[0215] 3. The dyne value of the carbon-coated layer surface of the carbon-coated aluminum foil for lithium batteries provided in Examples 1 to 8 and Comparative Examples 1 to 2 was tested by a dyne pen in accordance with the standard of GB / T 22638. The specific test method and judgment criteria are as follows:
[0216] Use dyne pens with different dyne values to draw an ink line of about 100mm on the surface of the carbon-coated layer, and observe the shrinkage of the ink strip on the carbon-coated aluminum foil. If the ink strip does not shrink within 2s and no small ink droplets appear, a dyne pen with a higher value should be selected for retesting until the ink line shrinks within 2s and small ink droplets appear. The value corresponding to the dyne pen with the previous value is the dyne value of the carbon-coated aluminum foil; if the ink strip drawn by the dyne pen initially selected shrinks within 2s and small ink droplets appear, a dyne pen with a lower value should be selected for testing until the ink strip does not shrink within 2s and no small ink droplets appear. The value corresponding to this dyne pen is the dyne value of the carbon-coated aluminum foil. The larger the dyne value, the better the adsorption capacity of the carbon-coated aluminum foil for the electrolyte and the positive electrode material. The final test results are shown in Table 1 below.
[0217] 4. A four-probe resistance tester was used to test the resistance of 10 positions around and in the center of the carbon-coated layer of the carbon-coated aluminum foil for lithium batteries provided in Examples 1 to 8 and Comparative Examples 1 to 2, and the average value was taken to obtain the surface square resistance value. The specific test results are shown in Table 1 below.
[0218] 5. The adhesion of the carbon-coated layer of the carbon-coated aluminum foil for lithium batteries provided in Examples 1 to 8 and Comparative Examples 1 to 2 on the aluminum foil was tested by the Hundred Grids method (GB / T 9286). The specific test method and judgment criteria are as follows:
[0219] During the test, a 11-tooth × 1mm cutter head was used to cut the surface of the carbon-coated aluminum foil in the horizontal, vertical and vertical directions to form a square array of 100 grids, and then 3M600 tape was used to adhere and pull it apart to observe the damage and peeling of the small grids. There was no damage or peeling on the edge of the grid, ISO grade 0, ASTM grade 5B; the actual damage and peeling area in the grid accounted for ≤5%, ISO grade 1, ASTM grade 4B; the actual damage and peeling area in the grid accounted for 5%-15%, ISO grade 2, ASTM grade 3B; the actual damage and peeling area in the grid accounted for 15%-35%, ISO grade 3, ASTM grade 2B; the actual damage and peeling area in the grid accounted for 35%-65%, ISO grade 4, ASTM grade 1B; the actual damage and peeling area in the grid accounted for ≥65%, ISO grade 5, ASTM grade 0B. The specific test results are shown in Table 1 below.
[0220] Table 1
[0221]
[0222] From the test results of Examples 1 to 3, it can be seen that the carbon-coated layer in the carbon-coated aluminum foil provided in Examples 1 to 3 of the present application has low surface square resistance and high conductivity on the first aspect; on the second aspect, it has a high dyne value, strong adsorption capacity for electrolyte, and good liquid retention capacity; on the third aspect, the carbon-coated layer has strong adhesion and is not easy to fall off, and the actual damaged and fallen area in the cross-section accounts for 0. Furthermore, as the content of the binder in the carbon-coated layer gradually increases, although the adhesion of the carbon-coated layer is improved, the surface square resistance also increases, and the dyne value decreases; the reason is: the increase in the binder content leads to a decrease in conductivity, the content of the material with oxygen-containing groups decreases, and the dyne value decreases.
[0223] By comparing the test results of Example 6 and Example 1, it can be learned that the carbon-coated layer in the carbon-coated aluminum foil provided in Example 6 has a significantly reduced surface resistance after being reduced by hydroiodic acid, the dyne value has increased, and the adhesion has decreased, indicating that hydroiodic acid effectively removes the oxygen-containing functional groups inside the carbon-coated layer, making its microstructure more loose and porous, so the dyne value increases and the adhesion decreases. This is because hydroiodic acid can cause the oxygen-containing groups such as hydroxyl groups in the carbon-coated layer to undergo a halogenation substitution reaction under the action of hydroiodic acid, thereby effectively removing the oxygen-containing functional groups in the carbon-coated layer, thereby reducing the surface resistance of the carbon-coated layer. Although the adhesion of the carbon-coated layer in the carbon-coated aluminum foil provided in Example 6 has decreased, resulting in a slight decrease in the stability of the carbon-coated layer, and the actual damaged and detached area in the grid accounts for 1%, but its surface resistance is significantly reduced, the dyne value is increased, the conductivity is greatly improved, and the adsorption of the electrolyte is also greatly improved.
[0224] Combining the test results of Example 1 and Comparative Example 1, as well as the scanning electron microscope image and infrared spectrum test, it can be known that the use of dilute nitric acid to modify GNP and CNT can effectively improve the stability and uniformity of the conductive paste. Specifically, the conductive filler in the conductive paste of Comparative Example 1 has not been treated with dilute nitric acid, and cannot be effectively loaded on the surface of the aluminum foil to form a uniform and stable conductive carbon-coated layer. Therefore, the surface square resistance of the obtained carbon-coated layer increases, and the dyne value is not significantly improved, and the adhesion is poor. This is because GNP and CNT have not been modified. On the one hand, they cannot be evenly dispersed on the surface of the aluminum foil. On the other hand, when the content of the binder used in the conductive paste is low, the unmodified GNP and CNT cannot form a stable network structure with other conductive materials, and it is difficult to adhere to the aluminum foil. The actual damaged and detached area in the grid is 21% as measured by the hundred-grid method.
[0225] Combining the test results of Example 1 and Comparative Example 2, compared with Example 1, the carbon-coated layer in the carbon-coated aluminum foil provided in Comparative Example 2 has a larger surface square resistance, no significant improvement in dyne value, and poor adhesion. The actual damaged and detached area in the cross-grids is 25% as measured by the 100-grid method. It can be seen that simple dilute nitric acid treatment can only graft a very small amount of oxygen-containing functional groups on the surface of GNPs and CNTs, which is not enough to make GNPs and CNTs stably dispersed in a mixed solvent. With the help of GO, as a dispersing aid, the dispersion effect can be effectively improved.
[0226] From the comparison of the test results of Example 1 and Example 8, it can be seen that when the mixed solvent whose pH is not adjusted to acidic is used, the surface square resistance of the carbon-coated layer in the carbon-coated aluminum foil is larger, the dyne value is not significantly improved, and the adhesion is also poor. The actual damaged and detached area in the cross-grid is 4% as measured by the 100-grid method. This indicates that the acidic solvent can not only effectively clean the oxide layer and oil stains on the surface of the aluminum current collector during the subsequent coating process, thereby reducing the interface resistance, but also react with the aluminum in the current collector to produce surface corrosion on the surface of the current collector, forming pits, and improving the subsequent adhesion to the carbon-coated layer.
[0227] The applicant declares that the present application illustrates the process of the present invention through the above-mentioned embodiments, but the present application is not limited to the above-mentioned process steps, that is, it does not mean that the present application must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement to the present application, equivalent replacement of the raw materials selected in the present application, addition of auxiliary components, selection of specific methods, etc., all fall within the scope of protection and disclosure of the present application.
[0228] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0229] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.
Claims
1. A carbon-coated current collector, characterized in that: The invention comprises a current collector body and a carbon coating layer covering at least one side of the current collector body along the thickness direction thereof, wherein the carbon coating layer comprises the following components: graphene oxide, modified graphene, modified carbon nanotubes, conductive carbon black and a binder in a mass ratio of (1-10):(10-45):(1-20):(1-10):(1-5), wherein the modified graphene and the modified carbon nanotubes both contain oxygen-containing groups.
2. The carbon-coated current collector according to claim 1, characterized in that: The oxygen-containing groups in the modified graphene and the oxygen-containing groups in the modified carbon nanotubes respectively include at least one of a hydroxyl group, a carboxyl group and a carbonyl group.
3. The carbon-coated current collector according to claim 1, characterized in that: The oxygen content in the carbon coating layer is 1% to 20%, and can be optionally 1% to 3%.
4. The carbon-coated current collector according to claim 1, characterized in that: The carbon-coated current collector meets at least one of the following conditions: (1) A micro-nano pit structure is formed on at least one side of the surface of the current collector body along the thickness direction; (2) The thickness of the current collector body is 4 μm to 20 μm; (3) The current collector body is a single-layer structure or a multi-layer composite structure; optionally, the single-layer structure is an aluminum foil, and the multi-layer composite structure includes a polymer layer and aluminum coatings disposed on opposite sides of the polymer layer in a thickness direction; (4) The thickness of the carbon coating layer is 0.5 μm to 5 μm; (5) The surface dyne value of the carbon coating layer is higher than 40 dyn; (6) The surface resistance of the carbon coating layer is less than 2.0Ω / sq.
5. A conductive paste, characterized in that: include: Graphene oxide, modified graphene, modified carbon nanotubes, conductive carbon black, binders and solvents; The mass ratio of the graphene oxide, the modified graphene, the modified carbon nanotube, the conductive carbon black, the binder and the solvent is (1-10): (10-45): (1-20): (1-10): (1-5): (3000-4000), and the modified graphene and the modified carbon nanotube both contain oxygen-containing groups.
6. The conductive paste according to claim 5, characterized in that: The modified graphene satisfies at least one of the following conditions: (1) The oxygen-containing groups in the modified graphene include at least one of hydroxyl, carboxyl and carbonyl; (2) The oxygen content in the modified graphene is 3% to 5%.
7. The conductive paste according to claim 5, characterized in that: The modified carbon nanotubes satisfy at least one of the following conditions: (1) The oxygen-containing groups in the modified carbon nanotubes include at least one of hydroxyl, carboxyl and carbonyl groups; (2) The oxygen content in the modified carbon nanotubes is 3% to 5%.
8. The conductive paste according to claim 5, characterized in that: The solvent includes: ethanol and water in a volume ratio of (1-10): (1-10); Optionally, the solvent further comprises an acid-base regulator, and the pH value of the solvent is 4-5; Optionally, the acid-base regulator includes at least one of sulfuric acid, nitric acid and acetic acid.
9. A method for preparing a conductive paste, characterized in that: include: Providing graphene oxide, modified graphene, modified carbon nanotubes and conductive carbon black, wherein the modified graphene and the modified carbon nanotubes both contain oxygen-containing groups; Adding the graphene oxide, the modified graphene, the modified carbon nanotube, the conductive carbon black and a binder into the solvent, and preparing the conductive slurry by dispersing, grinding and filtering; Wherein, the mass ratio of the graphene oxide, the modified graphene, the modified carbon nanotube, the conductive carbon black, the binder and the solvent is (1-10): (10-45): (1-20): (1-10): (1-5): (3000-4000).
10. The preparation method according to claim 9, characterized in that: The modified graphene is prepared by oxidation reaction of graphene and dilute nitric acid; The modified carbon nanotubes are prepared by oxidation reaction of carbon nanotubes and dilute nitric acid.
11. The preparation method according to claim 9, characterized in that: The solvent is prepared by mixing ethanol and water in a volume ratio of (1-10):(1-10), and then adjusting the pH of the mixed solvent to 4-5 with an acid-base regulator.
12. The preparation method according to claim 9, characterized in that: The preparation method satisfies at least one of the following conditions: (1) dispersing the graphene oxide, the modified graphene, the modified carbon nanotubes, the conductive carbon black and the binder by ultrasound; optionally, the frequency of the ultrasound is 20 KHz to 40 KHz, and the time is 0.5 h to 1 h; (2) The grinding is performed by sand milling, the grinding speed is 2000 rpm~3000 rpm, the grinding and mixing time is 3 h~24 h, and the grinding medium is 0.2 mm~2 mm zirconia beads.
13. A method for preparing a carbon-coated current collector, characterized in that: include: providing a current collector body; Coating the conductive paste according to any one of claims 5 to 8 on at least one side of the current collector body along the thickness direction thereof; The current collector body coated with the conductive slurry is dried, solidified and roll-pressed to prepare the carbon-coated current collector.
14. The preparation method according to claim 13, characterized in that: Before coating the conductive paste according to any one of claims 5 to 8 on at least one side of the current collector body along the thickness direction thereof, the method further comprises: Cleaning the surface of the current collector body to remove the oxide layer and oil stains on the surface of the current collector body; Optionally, the reagent used for the surface cleaning is a sodium hydroxide solution with a concentration of 10 g / L to 30 g / L, the cleaning temperature is 50° C. to 60° C., and the cleaning time is 0.5 h to 1 h; Optionally, the drying method is electric ceramic drying, and the drying temperature is 70°C to 80°C; Optionally, the coating method includes: at least one of spray coating, roller coating, dip coating, doctor blade coating, Meyer rod coating, electrospinning coating, and screen coating.
15. The preparation method according to claim 13, characterized in that: The preparation method further comprises: Performing a reduction treatment on the oxygen-containing groups in the carbon coating layer to remove the oxygen-containing groups in the carbon coating layer; Optionally, the reducing agent used in the reduction treatment is hydroiodic acid.
16. Use of the carbon-coated current collector according to any one of claims 1 to 4 in a secondary battery.
Citation Information
Cited By
Carbon-coated aluminum foil coating and preparation method thereof
CN120924096A